Pergeseran Fungsi Bregada Prajurit Keraton Surakarta - Tejo Bagus Sunaryo; Jussac Maulana Masjhoer (LIPI Press, 2023)
Bregada Surakarta palace is a military army that functions as a defence, security, and army of the Surakarta palace during colonialism in Indonesia. Bregada of the keraton Surakarta always experienced a shift in function in the post-independence period, especially during the leadership of King Paku Buwono XII. Although there has been a shift in function, the Surakarta palace troop still exists. This study aims to describe the process of shifting the function of the Surakarta palace warrior brigade. This research data uses literature review from historical records and ancient manuscripts and in-depth interviews with key informants. Based on the study results, the type of unit and the composition of the Surakarta Palace warrior brigade constantly changed from era to era. The brigades currently owned by the Surakarta Palace are the Music Corps, Tamtama, Jayeng Astra, Prawira Anom, Sarageni, Darapati, Jayasura, Baki, and Nyutra or Panyutra. The shift in the main functions of the Surakarta Palace Troops, as seen from the functions of the armed forces, defence and security, turned into traditional and cultural activities, mainly referring to their functions as performers of performing arts and tourism activists. Paku Buwono XIII, as a customary holder and successor to the previous king of the Surakarta palace, had a policy towards the sustainability of the Surakarta palace troupe. These policies include, among others, as a form of cultural preservation and adding to the activities of a soldier’s parade for the advancement of tourism in the city of Solo, Central Java.